PENGARUH PERAN ORANG TUA TERHADAP AKHLAK KARIMAH PADA ANAK USIA DINI KELOMPOK B DI TK BINAKHEIR CIBINONG KABUPATEN BOGOR - Edy; Siti Nurul Aulia (STIT Sirojul Falah Bogor, 2025)
This study aims to determine the effect of the role of parents on akhlak karimah in early childhood group B at Binakheir Kindergarten Cibinong, Bogor Regency. The importance of this research is in the role of parents in child development, especially in the formation of good morals in children such as teaching, habituation and proper guidance so that they can instill good morals in children. This study involved a research sample of 36 which was a sample of early childhood group B at Binakheir Cibinong Kindergarten. The research used by researchers is quantitative type with references to journals, books and the web as well as data collection through observation, questionnaires, progress reports and documentation. The results of data analysis show that there is a positive influence between the role of parents and akhlak karimah in early childhood group B at Binakheir Kindergarten. Then it is concluded that the results of this study are by obtaining a rcount value of 0.70 and with a significant level of 5%, an rtable value of 0.33 is obtained. Thus, rcount ≥ rtable (0.70 ≥ 0.33), then the alternative hypothesis is accepted, while the null hypothesis is rejected, meaning that there is a significant relationship between the role of parents and good morals in early childhood at Binakheir Cibinong Kindergarten, Bogor Regency. The role of parents has a significant influence on akhlak karimah in early childhood group B at Binakheir Kindergarten Cibinong, Bogor Regency. This study provides input for parents to be more aware of their role in teaching, modeling and guiding in educating their children so that they can have good morals.